Kemampuan Pemecahan Masalah Usaha Dan Energi Peserta Didik Kelas X Dengan Model Learning Cycle 7E - Nuzulia, Chantika Rizki; Ayub, Syahrial; Harjono, Ahmad; Doyan, Aris (Universitas Hamzanwadi, 2023)
This study is aimed to investigate the effect of Learning Cycle 7E model on the physics problem-solving abilities (PSA) of students. This study is an experimental research with a non-equivalent control group design. The population is all students of class X MIPA SMAN 3 Selong. The sampling technique was purposive sampling in which class X MIPA 4 class as the experimental class and X MIPA 1 as the control class. The experimental class was treated with Learning Cycle 7E model, while the control class was given a conventional learning. Before and after being treated, both classes were given a PSA test which amounted to 5 questions. The results of the initial and final PSA tests were analyzed for homogeneity and normality to conduct hypothesis testing. Hypothesis test analysis shows that is rejected and is accepted, so it can be concluded that there is an effect of the Learning Cycle 7E model on students' physics problem solving.